English writing : a critical review - Gautam, G. S. (Gyan Singh), 1958-; Saxena, M. C.; All India English Teachers' Conference 2001 : Government Hamidia College) (New Delhi : Classical Pub., 2012)
Papers presented at the 45th All India English Teachers' Conference, held at Bhopal in 2001
Includes bibliographical references.
Keywords: English literature -- History and criticism -- Congresses